The Novel Association of the Chemokine CCL22 with Abdominal Aortic Aneurysm - Golledge, Jonathan (American Society for Investigative Pathology, 2010)
The aim of this study was to examine aortic biopsies with a cytokine array to identify new cytokines associated with abdominal aortic aneurysm (AAA). We assessed the relative expression of 79 cytokines using antibody-based cytokine arrays in a total of 12 AAA and 12 control aortic biopsies. Based on these findings we validated the findings for one cytokine by examining a further 11 AAA and 11 atherothrombosis biopsies and serum from 1028 men, 315 of whom had an AAA. Three cytokines (interleukins 1B and 8, and Chemokine CC motif ligand 22 [CCL22]) were consistently up-regulated in AAA biopsies. Since CCL22 had not previously been associated with aortic dilatation, we confirmed the upregulation of this cytokine in further tissue biopsies and serum using enzyme-linked immunosorbent assay. Median serum concentrations of CCL22 were greater in men with AAA (0.69 ng/ml) than controls (0.56 ng/ml, P < 0.01). Serum CCL22 was independently associated with both small (OR 1.51, 95% CI 1.21–1.88) and large AAA (OR 1.33, 95% CI 1.08–1.62) after adjusting for other risk factors. The association between CCL22 and AAA was also confirmed using immunohistochemistry. The results presented in this study demonstrate a novel association between CCL22 and AAA as well as illustrate how a protein array can be used to identify novel markers of potential pathogenic and diagnostic significance for AAA.